The Effect of Deep Tissue Massage on Lactate Clearance Kinetic and Muscle Strength Recovery - Vlasov, Maksym (Академічні візії, 2026)
Relevance of the study. The relevance of this study is determined by the increasing intensity and density of training and competitive loads in modern sport, which significantly raise the requirements for effective post-exercise recovery. One of the key physiological markers of muscular fatigue is lactate accumulation, the clearance kinetics of which are closely associated with the restoration of muscle strength and readiness for repeated physical efforts. Despite the widespread use of deep tissue massage in sports medicine and physical therapy, its effects on lactate clearance dynamics and functional muscle recovery remain insufficiently systematized and require experimental justification. Purpose of the study. The purpose of this article was to experimentally determine the effect of deep tissue massage on blood lactate clearance kinetics and the recovery of muscle strength after intense physical exercise in order to substantiate effective approaches to optimizing recovery interventions in sport and physical therapy. Methods. The study was conducted as a controlled comparative experiment with repeated measurements. A standardized high-intensity exercise protocol was applied, followed by recovery either with deep tissue massage or passive rest. Blood lactate concentration and muscle strength indicators were assessed at fixed time points during the post-exercise period. Experimental conditions, testing procedures, and recovery protocols were standardized to ensure the reliability and objectivity of the results. Results. It was established that the application of deep tissue massage was associated with a faster reduction in blood lactate concentration during the early post-exercise recovery period compared with passive rest. It was demonstrated that accelerated metabolic recovery was accompanied by higher rates of muscle strength restoration within 10–30 minutes after exercise. A time-dependent specificity of the massage effect was identified, indicating its functional relevance for subsequent physical performance. Conclusions. The findings indicate that deep tissue massage is an effective post-exercise recovery modality influencing not only subjective fatigue perception but also objective metabolic and strength-related parameters. The feasibility of its selective and individualized application depending on the characteristics and intensity of physical loads was substantiated. Prospects for further research. Further studies should focus on clarifying dose-dependent effects of deep tissue massage, developing objective criteria for controlling mechanical stimulation intensity, and investigating the long-term influence of massage on adaptive processes and the stability of muscular performance.